Do we experience pandemic fatigue? current state, predictors, and prevention - Haktanir, Abdulkadir; Can, Nesime; Seki, Tolga; Kurnaz, M. Furkan; Dilmaç, Bülent (Current psychology (New Brunswick, N.J.), 2022)
There is an emerging literature on the mental and physical exhaustion due to the COVID-19 related restrictions. Some individuals seem to exercise fewer precautions recently in comparison to the onset of the pandemic in preventing the spread of the COVID-19. This phenomenon is described as pandemic fatigue. Though acknowledged in conceptual articles and news reports, there is a lack of empirical evidence pertaining to pandemic fatigue. We collected data from 516 adult participants to investigate pandemic fatigue and its relations to fear of coronavirus, intolerance of uncertainty, apathy, and self-care. 34.40% of the participants reported that the level of COVID-19-related precautions they take have decreased in comparison to measures they took at the onset of the pandemic. Additionally, our model examining the role of fear of coronavirus, intolerance of uncertainty, and apathy as mediated by self-care predicting pandemic fatigue demonstrated acceptable to excellent goodness-of-fit indices. The fact that one in every three individuals is taking fewer precautions is not only a threat to the individuals’ own health but also to the public. Given that individuals are experiencing pandemic fatigue, governments should consider paying more attention to the biopsychosocial nature of humans in ordering restrictions and planning necessary precautions.